Identification of the Potential of Bali Oka Wedding Organizer as a Supporting Product for MICE Tourism in Bali - Devi Triana Puspa; Susanti, Putu Herny; Firman Sinaga (International Journal of Educational Research Excellence, 2026)
Bali Oka Wedding Organizer integrates traditional Balinese wedding ceremonies with modern service standards, positioning itself not only as a wedding service provider but also as a cultural attraction that contributes to incentive tourism and event tourism. The research employs a descriptive qualitative approach combined with SWOT analysis, using online questionnaires distributed to clients, vendors, internal crews, and both domestic and international tourists. Findings reveal that the main strengths of Bali Oka lie in operational stability, service digitalization, and strong support from local communities and artists. Weaknesses include limited cultural-based certification, vendor coordination issues, and inconsistent global branding. External factors present significant opportunities through destination wedding trends, government support, and multi-stakeholder collaboration, while threats arise from competition with international wedding organizers and limited digital promotion. The identification highlights Bali Oka Wedding Organizer’s strategic role as a supporting product for MICE Tourism in Bali, with recommendations to strengthen branding, enhance human resource competencies, and optimize digitalization to remain competitive in the global wedding tourism market.